A rare ectopic localization of pleomorphic adenoma of lip - Kumar, Birbal; Gupta, Balkishan; Mitra, D. S. (International Surgery Journal, 2024)
This case report described a rare and unusual lesion found in a 68-year-old male, which was diagnosed as pleomorphic adenoma of the minor salivary glands in the upper lip. The tumor was a circumscribed, large firm mass, about 2 cm in diameter, characterized by slow growth. Complete excision was performed and the histopathologic analysis showed pleomorphic adenoma.